Ontogeny and brooding strategy of the early Cambrian arthropod Isoxys minor from the Qingjiang biota - Ma, Jiaxin; Pates, Stephen; Wu, Yu; Lin, Weiliang; Liu, Cong; Wu, Yuheng; Zhang, Mingjing; Fu, Dongjing (Frontiers in Ecology and Evolution, 2023)
†Isoxys is a worldwide distributed bivalved arthropod known almost exclusively from Cambrian Burgess Shale-type Lagerstätten. Outline analyses using 34 specimens of the iconic large bivalved arthropod †Isoxys minor from the Cambrian Stage 3 (~518 Ma) Qingjiang biota and the Cambrian Stage 4 Guanshan biota, interpret that they are the same species and there is a very slight difference in the shape of the outlines of the carapaces between the two biotas. This suggests that environment might be driving intraspecific variation. Quantitative analysis of shape changes during growth using 51 specimens of †I. minor from the Qingjiang biota, reveals that its valves gradually elongate and the ratio of cardinal spines and spherical eyes relative to the valve length significantly decreases during postembryonic development. †I. minor has proportionally large cardinal spines and eyes in the earliest stages, and this allometric growth is beneficial for self-protection and foraging, which may have improved the survival rate of individuals with these characters. In addition, two of the specimens document the evidence of brood care in †I. minor, and the egg cluster occupies almost the entire dorsal region under the carapace. Compared to other early Paleozoic egg-carrying arthropods, †I. minor broods have the highest number (~300 per clutch) of small (Ø, ~0.5 mm) eggs. Since the ovigerous individuals are almost half the size of the adults, †I. minor may have possessed reproductive ability during the early life stage. The results indicate that spines played an antipredatory role for †I. minor, and that it followed an r-strategy of reproducing with many individuals at an early stage. †I. minor also represents the earliest diverging arthropod from which brood care has been documented.